2023
DOI: 10.1186/s12974-023-02899-3
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic shift during West Nile virus infection provides new therapeutic opportunities

Patricia Mingo-Casas,
Ana-Belén Blázquez,
Marta Gómez de Cedrón
et al.

Abstract: Background Viral rewiring of host bioenergetics and immunometabolism may provide novel targets for therapeutic interventions against viral infections. Here, we have explored the effect on bioenergetics during the infection with the mosquito-borne flavivirus West Nile virus (WNV), a medically relevant neurotropic pathogen causing outbreaks of meningitis and encephalitis worldwide. Results A systematic literature search and meta-analysis pointed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…This can be driven by adiponectin or its pharmacological analog AdipoRon with benefits at different levels. Like in a recent study on new therapeutic opportunities to fight West Nile Virus [86], our study demonstrates the value of antiviral molecules targeting the potentiation of responses and metabolic orientation of the host cells rather than targeting the virus particle or viral factors involved in the viral cycle.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This can be driven by adiponectin or its pharmacological analog AdipoRon with benefits at different levels. Like in a recent study on new therapeutic opportunities to fight West Nile Virus [86], our study demonstrates the value of antiviral molecules targeting the potentiation of responses and metabolic orientation of the host cells rather than targeting the virus particle or viral factors involved in the viral cycle.…”
Section: Discussionsupporting
confidence: 65%
“…It therefore appears that viruses have strategies to favor the glycolytic use of glucose instead of OXPHOS, to increase viral production and limit antiviral response. In this regard, ZIKV and a few other flaviviruses are known examples of viruses that promote metabolic reprogramming to their benefit [ 82 , 83 , 84 , 85 , 86 ]. Indeed, the AMPK system is a sensor of cellular energy status that responds primarily to changes in the AMP:ATP ratio and activated OXPHOS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a proof of concept study demonstrated the druggability of the glycolytic pathway during WNV infection, with pharmacological inhibitors of glycolysis reducing neuroinflammation in a mouse model of WNV infection. 55 While this may be protective to prevent pathogenic immune responses coordinated by specific cell subsets such as brain-infiltrating macrophages which promote CNS damage, this can also inhibit protective virus clearance functions by NK cells. Cell-specific metabolic inhibitors are thus required to target pathogenic cells fueled by glycolysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, hexokinase inhibitors such as 2-deoxyglucose (2DOG) or 3-bromopyruvate, as well as the lactate dehydrogenase inhibitor oxamate, have been scrutinized as potential antiviral agents, and notably, 2DOG underwent phase II trials on COVID-19 patients [ 49 ]. DCA has been shown to be effective against hepatitis viruses in established tumour cell lines [ 50,51 ], West Nile virus infections in the brain of mice [ 52 ] or SARS-CoV-2 in isolated human kidney cells [ 53 ]. Therefore, the data available reinforces the role of glycolysis, and particularly PDKs, in the viral-induced hijacking of cellular metabolism, pointing to DCA as a broad-spectrum antiviral.…”
Section: Discussionmentioning
confidence: 99%